The - Giovanni Dosi; Richard R. Nelson; Sidney G. Winter (Oxford University Press, 2000)
In this book, the editors and a team of distinguished international contributors analyse the nature of organizational capabilities--how organizations do things, use their knowledge base, and diffuse that knowledge in a competitive environment